ANALYSIS OF INHERITANCE DISTRIBUTION AMONG MINANG COMMUNITY AGAINST HIGH HERITAGE AND LOW HERITAGE - Faridha, Erlin; Wiranata, I Gede AB; Rodliyah, Nunung (Faculty of Law, Universitas Lampung, 2024)
This research aimed to examine and analyze the distribution of inheritance within the Minangkabau ethnic community, focusing on the application of customary law. Due to a lack of understanding regarding the proper division of customary inheritance, discrepancies and conflicts frequently arose during the process. This qualitative research employed an empirical descriptive approach and was conducted in Bandar Jaya Barat Village, Central Lampung Regency. The research utilized both primary and secondary data, collected through fieldwork and literature review. The findings revealed that inheritance distribution in the Minangkabau community of Bandar Jaya Barat followed two systems: the matrilineal collective inheritance system and the bilateral individual inheritance system. High inheritance was distributed using the matrilineal collective system, while low inheritance, particularly in Bandar Jaya Barat, was distributed through the bilateral individual system, which did not require approval from Minangkabau customary leaders.